KENDALA GURU DALAM MENERAPKAN MODEL-MODEL PEMBELAJARAN BERDASARKAN KURIKULUM 2013 PADA SD NEGERI 62 BANDA ACEH. - Mislinawati Mislinawati.; Nurmasyitah Nurmasyitah. (Jurnal Pesona Dasar, 2018)
This study aims to determine the constraints faced by teachers at implementing learning models based on the 2013 curriculum at SD Negeri 62 Banda Aceh. The approach used at this study is qualitative. The subject of SD 62 Banda Aceh teacher research was 20 people. Data collection is done by observation techniques through mentoring learning and interviews. Furthermore, all data is processed with the stages of qualitative data analysis, namely data reduction, data presentation, and drawing conclusions. Based on the results of data analysis, the constraints faced by teachers at implementing the 2013 curriculum learning model is in preparing the lesson plan (RPP) the teacher writes the learning model, but the teacher does not write down the syntax in the model, this is because the teacher does not understand the learning steps accordingly the syntax that exists in the learning model. so that teachers are less able to stimulate students to find out for themselves the problems that exist in the learning material, in fact the role of teachers is more dominant than students. Students are not given the opportunity to find their own concepts that are being discussed, as well as in the classroom management teachers are less able to direct students who are less able to be actively involved, and teachers do not get around the available time. The conclusions of this study are that the teacher has not applied the suggested learning in the 2013 curriculum because the teacher does not understand the existing syntax so they less motivated to implement it.